Ontogenetic diet shift in Commerson’s dolphin (Cephalorhynchus commersonii commersonii) off Tierra del Fuego - Riccialdelli, Luciana; Newsome, Seth Darnaby; Dellabianca, Natalia Andrea; Bastida, Ricardo Oscar; Fogel, Marilyn; Prosser Goodall, Rae Natalie (Polar Biology)
The Commerson´s dolphin (Cephalorhynchus c. commersonii, Lacépède, 1804) is the most common endemic dolphin from the coastal waters of Tierra del Fuego incidentally caught in artisanal coastal gill nets. A better understanding of its trophic ecology is essential to facilitate the effective management and conservation of it population. The aim of this study was to analyze possible shifts in diet among age and sex classes by analyzing bone collagen δ13C and δ15N values collected from 220 individuals along the coast of Tierra del Fuego. Additional analysis of potential prey allowed us to use a stable isotope mixing model to quantify resource use. Isotopic comparisons suggest that all age classes share the same foraging areas. We found, however, a significant dietary shift, juveniles consume a higher mean (±SD) proportion (60±7%) of pelagic Sprattus fuegensis than adults (36±10%), and the consumption of benthopelagic species such as Illex argentinus and Loligo gahi is higher in adults (33±12%) than juveniles (20±7%). This may result from an improvement in foraging skills and expansion of habitats to adulthood. While males move greater distances in search of mates and resources a lack of isotopic differences between the sexes suggests little evidence for sex-related resource partitioning. A significant decrease in δ15N values between calves and juveniles indicate a weaning period between 0.5 to 1 year as was shown in previous captive studies on this species. Our results also suggest that artisanal fisheries, despite being a major source of mortality, do not affect the long-term food habits of Commerson´s dolphin since they showed a weak trophic overlap. Fil: Riccialdelli, Luciana. Museo Acatushún de Aves y Mamíferos Marinos Australes; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Newsome, Seth Darnaby. University of Wyoming. Department of Zoology and Physiology; Estados Unidos. Consejo Nacional de Investigaciones Científicas y ...